The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s10973-011-1479-8
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal and solution calorimetry to assess the effect of superplasticizers and mineral admixtures on cement hydration

Abstract: The heat of hydration evolution of eight paste mixtures of various water to binder ratio and containing various pozzolanic (silica fume, fly ash) and latent hydraulic (granulated blast furnace slag) admixtures have been studied by means of isothermal calorimetry during the first 7 days of the hydration process and by means of solution calorimetry for up to 120 days. The results of early heat of hydration values obtained by both methods are comparable in case of the samples without mineral admixtures; the value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 29 publications
3
26
0
2
Order By: Relevance
“…Addition of fly ash more distinctly retards the acceleratory period of cement hydration than slag, this tendency is especially clear for the high substitution rate of fly ashes. This retarding effect of the mineral additions on the cement hydration has been already reported [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Addition of fly ash more distinctly retards the acceleratory period of cement hydration than slag, this tendency is especially clear for the high substitution rate of fly ashes. This retarding effect of the mineral additions on the cement hydration has been already reported [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Resultssupporting
confidence: 67%
“…It has been observed in these tests that the evolved heat decreases as slag content increases, but at the same time the heat evolved increases with the fineness of the slag or clinker in the blended cements. Simultaneously, mixtures containing GBFS do not generate higher heat initially, but they generate heat higher than the OPC pastes in the later period [24]. The tests performed at different temperature showed that higher curing temperature increased the reactivity of the slag and a decreased reactivity with an increase in the percentage of slag replacement.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Subsequently, the heat evolution was monitored for the mixtures composed of 25 % fly ash and 75 % cement CEM I samples. The calorimetric measurements appeared again as a convenient, rapid method of the hydraulic activity assessment, used in case of mineral additives and different modifying agents for a couple of years [15][16][17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…Besides these effects, the reduction in particle size by grinding can boost the effect of heterogeneous nucleation, due to the inclusion of new nucleation sites for deposition of the hydrated products [8][9][10][11][12]. Grinding can also be responsible for promoting partial amorphization and significant increase in specific surface area [5][6][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%